Treatment of Cornea and Ocular Surface Diseases - Scorcia, Vincenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on the comprehensive understanding and novel treatments in the realm of cornea and ocular surface diseases. Ranging from the relatively benign manifestations of keratoconjunctivitis sicca to more critical conditions such as corneal ulcers, ocular surface diseases pose a considerable challenge in clinical ophthalmology. Such conditions can severely compromise the transparency of the cornea, often necessitating interventions such as keratoplasty. A significant emphasis of this edition is on the paramount importance of pre-surgical optimization. A successful keratoplasty is often predicated on the health of the ocular surface. Through a series of insightful articles, the importance of enhancing tear function, rehabilitating the normal lid anatomy, and ensuring a robust limbal stem cell supply is elucidated. Properly addressing these factors has a direct bearing on the success rate of the subsequent surgical intervention. Another highlight of this Special Issue is the presentation of cutting-edge treatments. Researchers from around the globe share their findings, detailing advancements in both surgical and non-surgical treatments. These range from innovative surgical techniques and tools to groundbreaking pharmaceutical agents that hold promise in managing and possibly reversing some of these conditions. In summary, this Special Issue serves as a repository of the latest knowledge in the management of cornea and ocular surface diseases, aimed at both the seasoned ophthalmologist and budding researchers in the field.